GPT Chat with Project-Based Learning in Learning: A Review - Yusuf, Mashuri (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
The advancement of technology in education has created opportunities for creative pedagogies. One such ground-breaking technology is ChatGPT, a learning model created by Open AI, which has enormous potential to boost productivity while also enhancing pedagogy for more captivating educational opportunities. This study aims to evaluate how well GPT Chat integrates with project-based learning. The Preferred Reporting Items for Review method was used in this study. The study's findings clarify that educational institutions need to prepare students for new forms of literacy in the fields of data, technology, and human resources in the context of the Industrial Revolution Era 4.0. Project-based learning is an approach to education that emphasizes students working together to solve a variety of problems through a sequence of steps that include information collection, project planning, and the production of a specific result that is packaged as project work. Determining fundamental questions, creating a project plan, creating a timeline, monitoring, testing findings, and experience evaluation are the phases of project-based learning. ChatGPT is a "thought partner" and research tool that can be used for many different types of educational activities. In Indonesia, the PjBL model's implementation may enhance students' motivation and academic performance. Thus, to significantly improve the standard of education and student motivation in Indonesia, more attention needs to be paid to the integration of GPT chat with project-based learning.